# Answer to Question #10936 in Matrix | Tensor Analysis for srijita

Question #10936

suppose A and B are square matrices that satisfy AB+BA=0 where 0 is a square matrix of zeroes. Then it must be that

a) (A^2)(B^3)=(B^3)(A^2)

b)(A^2)(B^3)=(B^2)(A^3)

c)(A^2)(B^3)=(B)(A^4)

d)none

a) (A^2)(B^3)=(B^3)(A^2)

b)(A^2)(B^3)=(B^2)(A^3)

c)(A^2)(B^3)=(B)(A^4)

d)none

Expert's answer

#### Not answered

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment